Critical potassium dilution curve for potato crops - Sandaña, Patricio; Soratto, Rogério P. [UNESP]; Silva, Júlio César de A. [UNESP]; Valenzuela, Alfonso; Parecido, Renan J. [UNESP]; Fernandes, Adalton M. [UNESP]; Ciampitti, Ignacio A. (Elsevier, 2024)
Context or problem: Proper potassium (K) nutrition is a key management factor to attain both high tuber yields and quality in potato (Solanum tuberosum L.) crop. Therefore, developing diagnostic tools to assess crop K status via utilization of a critical K dilution curve (Kcr = aW-b) and calculation of the K nutrition index (KNI) is essential to advance K fertilization management in potato crops. Objective or research question: The aims of this study were to: (i) compute and compare different critical K dilution curves via a hierarchical Bayesian approach for different genotype × environment × management (G × E × M) scenarios and (ii) assess the relationship between tuber yield and K nutrition index (KNI) tested under diverse G × E × M scenarios. Methods: Five field experiments were conducted in Brazil (exp. 1 and 2) and Chile (exp. 3–5) during the 2020–2022 growing seasons, using four to five K fertilization rates (0–500 kg K ha−1) and two cultivars (Asterix or Patagonia-INIA). A hierarchical Bayesian approach was applied to quantify the parameters of the dilution curve and their uncertainties under eight G × E × M scenarios. Results: From all those curves, a generic critical dilution K curve was established under those scenarios [(Kcr (%) = 6.32 W−0.27)], for a broad range of variation of total fresh tuber yield (27–98 Mg ha−1), total dry plant biomass (1.1–22.6 Mg ha−1), and plant K concentration (1.3–6.9 %). The integrated KNI described the relative tuber yield (RY) significantly (p < 0.01; R2 = 0.78) by a linear function, reaching the maximum RY with a KNI value of 1. Furthermore, a similar pattern was observed between RY and instantaneous KNI calculated from one sample date from an independent dataset. Conclusions: A generic critical dilution curve for K was determined as the best model across different G × E × M scenarios. Thus, supporting the concept of using a generic K dilution curve rather than specific curves for different cultivars and/or environments. Implications or significance: This critical K dilution curve is a valuable tool for quantifying KNI and improving the effective use of this nutrient for potato production systems under diverse environments.
Keywords: Bayesian; Concentration; KNI; Solanum tuberosum; Tuber